2019
DOI: 10.2106/jbjs.oa.18.00058
|View full text |Cite
|
Sign up to set email alerts
|

Posterior Malleolar Ankle Fractures

Abstract: Background: There is increasing acceptance that the clinical outcomes following posterior malleolar fractures are less than satisfactory. We report our results of posterior malleolar fracture management based on the classification by Mason and Molloy. Methods: All fractures were classified on the basis of computed tomographic (CT) scans obtained preoperatively. This dictated the treatment algorithm. Type-1 fractures underwent syndesmotic fixation. Type-2A fractures unde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(22 citation statements)
references
References 24 publications
1
15
0
Order By: Relevance
“… 9 , 10 , 33 , 35 , 44 , 55 Other authors recommend ORIF of all PMFs regardless of their size as this this was found to reduce the need for syndesmotic fixation and improve outcomes in their study. 3 , 23 , 29 , 30 The subanalyses of patients with PMF smaller than 25% in the current study displayed similar SEFAS scores between treatment groups, although fragments were fixed in group A and no fixation was performed in group B. There was a trend of better results in group B.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“… 9 , 10 , 33 , 35 , 44 , 55 Other authors recommend ORIF of all PMFs regardless of their size as this this was found to reduce the need for syndesmotic fixation and improve outcomes in their study. 3 , 23 , 29 , 30 The subanalyses of patients with PMF smaller than 25% in the current study displayed similar SEFAS scores between treatment groups, although fragments were fixed in group A and no fixation was performed in group B. There was a trend of better results in group B.…”
Section: Discussionsupporting
confidence: 52%
“…Compared to the normative values of SEFAS, 8 our results of median 36 for group A and 40 for group B reflect the serious impact on function and quality of life of an ankle fracture involving the posterior malleolus. Mason et al 29 also reported low PROM scores in patients with posterior malleolus fractures, with a mean Olerud-Molander Ankle Score of 74.1. Xu et al 56 found an average American Orthopaedic Foot & Ankle Society (AOFAS) score of 95.9 in a similar population.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…We believe characterizing the fracture pattern, utilizing the Mason and Molloy classification, will help plan a stable fixation strategy. 9,38,39 We have found that those with a Mason and Molloy classification type 1, type 2a, and posterolateral portions of 2b can effectively be approached by a posterolateral approach. The posteromedial portion of type 2b's are best approached by a medialposteromedial approach and type 3s are best approached by a posteromedial approach.…”
Section: Discussionmentioning
confidence: 97%
“… 121 According to the Mason classification, Mason Type 2 and 3 posterior malleolar fractures are treated with a posterolateral approach and only Type 1 fractures with trans-syndesmotic fixation. 125 The posterolateral approaches allow open reduction and internal fixation of the posterior malleolus as well as the treatment of distal fibular fractures. 99 Open reduction and internal fixation of the posterior malleolus can be performed with posterior screw or plate fixation depending on the fracture configuration and bone quality.…”
Section: Operative Treatmentmentioning
confidence: 99%